Satisfação dos Usuários do Ambulatório Geral do Hospital das Clínicas de Botucatu - Santos, Gabriela Antonio dos [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The searches for a health service it’s a part of a process, searches for a qualified evaluation can arise the perception, in form of irritating factors taking for an alert state. The personal expectation, it makes influence in its perceptions, too. The objective was to evaluate the satisfaction degree of the users of “Seção Técnica de Ambulatório Geral do Hospital das Clínicas de Botucatu”. The work is about a quantitative and transversal study, with calculated sample of 366 users, chosen randomly and invited to participate through a questionnaire. The population was compounded by a majority of women (64,5%), between 50 to 59 years old and average degree of education (38,3%). 25 specialties were cited. The evaluate about comfort, cleaning, reception, waiting time, medical attention and nursing vary between “very good” and “good”. Obtained significant “regular” assessment, the comfort in the waiting rooms (24%), silence (25%) and cleaning bathroom (63%). Others negative evaluation was the reception about the waiting time (26%), waiting time between arrival and the consultation (34%), waiting time between the request and consultation (27%). 30,6% report to know the place for complaints and 79,4% of these pointed to the ombudsman. 62% consider their problems solved, 84,4% would indicate the hospital, 57,4% would consider the hospital better than imagined. 42,62% used the opened area for thanking, critical for staff, suggestion infrastructure improvements, cleaning and waiting time. The biggest complaint was the staff turnover in the treatment. There was disharmony between the objective and subjective questions, but, all of them must be considered to propose improvements. The satisfaction evaluation makes the service more effective, bringing credibility to the health service and the patients adhere better to the treatment

A procura por um serviço de saúde (SS) faz parte de um processo; a busca por avaliação qualificada aflora a percepção, sob a forma de fatores estressantes, levando a um estado de alerta. As expectativas pessoais também influenciam na percepção. O objetivo foi avaliar o grau de satisfação dos usuários da Seção Técnica de Ambulatório Geral do Hospital das Clínicas de Botucatu. Trata-se de um estudo quantitativo e transversal, com amostra calculada de 365 usuários, escolhidos aleatoriamente e convidados a participar por meio de questionário. A população foi composta por uma maioria de mulheres (64,5%), entre 50 a 59 anos e grau médio de escolaridade (38,3%). 25 especialidades foram citadas. As avaliações quanto ao conforto, limpeza, recepção, tempo de espera, atendimento médico e de enfermagem, variaram entre muito bom e bom. Obtiveram avaliação regular significativa o conforto nas salas de espera (24%), silêncio (25%) e limpeza dos banheiros (63%). Outras avaliações negativas foram recepção quanto ao tempo de espera (26%), tempo de espera entre a chegada e realização da consulta (34%), tempo de espera entre o pedido e realização da consulta (27%). 30,6% referiram saber o local para reclamações e destes, 79,4% apontaram a ouvidoria. 62% consideraram seus problemas resolvidos, 84,4% indicariam o hospital, 57,4% consideraram o hospital melhor do que imaginavam. 42,62% utilizaram espaço aberto para agradecimentos, críticas às equipes, sugestões de melhorias na infra-estrutura, na limpeza e no tempo de espera. A maior queixa foi à rotatividade da equipe nos atendimentos. Houve desarmonia entre questões objetivas e subjetivas, entretanto, todas devem ser consideradas para propor melhorias. A avaliação de satisfação torna o atendimento mais eficaz, trazendo credibilidade aos SS e os pacientes aderem melhor ao tratamento
Keywords: Serviços de promoção da saude; Serviços de saude; Pacientes; Satisfação; Serviço ao cliente - Qualidade